Operational Efficiency Assessment of PT Asuransi Jasa Tania Tbk: Analyzing Operating Expense to Revenue Ratio - Idamanis Laia; Dyah Palupiningtyas (Universitas Sains dan Teknologi Komputer, 2025)
This study aims to evaluate the operational efficiency of PT Asuransi Jasa Tania Tbk in 2023 using the operating expense to revenue ratio (Expense Ratio). The data used is the company's financial statements for the year ended December 31, 2023. The results show that PT Asuransi Jasa Tania Tbk successfully improved its operational efficiency significantly, with a decrease in the Expense Ratio by 17.24% to 48% compared to the previous year. This efficiency improvement was driven by strong net premium income growth, effective operating expense control, and investments in digitalization. Compared to the general insurance industry average in Indonesia, PT Asuransi Jasa Tania Tbk demonstrates a better level of efficiency. These findings highlight the importance of operational efficiency for the profitability and competitiveness of insurance companies, as well as the relevance of technology adoption in enhancing efficiency. Practical and theoretical implications are discussed.